2021
DOI: 10.14744/hf.2021.2021.0020
|View full text |Cite
|
Sign up to set email alerts
|

An overview of SARS-COV-2 related hepatic injury

Abstract: Severe acute respiratory syndrome coronavirus 2, the causative pathogen of coronavirus disease 2019 (COVID-19), is highly contagious and has led to a variety of clinical manifestations including liver injury. Although, there have been a few reports indicating acute-on-chronic liver failure among COVID-19 patients, the patients with COVID-19 related liver injury are generally asymptomatic and present with mild to moderate elevation in serum hepatic enzymes.In this article, we aimed to summarize the current lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Previous observations revealed that enzymatic features of liver disorder accompanying COVID-19 might predict a more severe course of the disease, poorer overall outcome and a higher rate of mortality [151][152][153][154][155]. In general, individuals affected with SARS-CoV-2 infection usually present a hepatocellular pattern of liver injury (with a threefold increase in aminotransferases above the upper limit of normal (ULN)) or a mixed one (hepatocellular pattern together with a twofold increase in ALP/GGT) [156]. Fulfilling the above-mentioned criteria indicated a significant risk of more severe presentation due to COVID-19.…”
Section: Covid-19 In Patients Without Previously Diagnosed Liver Diso...mentioning
confidence: 99%
“…Previous observations revealed that enzymatic features of liver disorder accompanying COVID-19 might predict a more severe course of the disease, poorer overall outcome and a higher rate of mortality [151][152][153][154][155]. In general, individuals affected with SARS-CoV-2 infection usually present a hepatocellular pattern of liver injury (with a threefold increase in aminotransferases above the upper limit of normal (ULN)) or a mixed one (hepatocellular pattern together with a twofold increase in ALP/GGT) [156]. Fulfilling the above-mentioned criteria indicated a significant risk of more severe presentation due to COVID-19.…”
Section: Covid-19 In Patients Without Previously Diagnosed Liver Diso...mentioning
confidence: 99%